Hydrothermal incubation-induced amyloid fibrillation of wheat gluten peptide: regulation of functional properties via multi-scale structural and morphological evolution - Yuwen Wang; Mengyuan Li; Zheng Wang; Lingfang Zhang; Binghua Sun; Sen Ma (Food Hydrocolloids, 2027)

Molecular epidemiology and antimicrobial resistance of Vibrio parahaemolyticus isolates from aquatic products in the Southern Fujian coast, China - Qiao-Hua Zheng; Yang Chen; Yu-Fang Tian; Turmidzi Fath; Jun-Chao Zheng; Dan-Feng Zhang; Yi-Hong Wang; Qing-Sen Chen; Feng-Xia Li; Xiu-Min Chen; Yuan-Qing Hu (Brazilian Journal of Microbiology, 2026)

Acrylamide formation in baked foods: Dietary fiber-driven mitigation strategies and mechanistic insights - Zheng Wang; Mengyuan Li; Sen Ma (Trends in Food Science & Technology, 2026)

Three-dimensional site response and dynamic stress concentration around a spherical cavity in an unsaturated porous half-space under SV-wave incidence - Zhe Yang; Weihua Li; Sen Zheng; Yexin Wan; Sainan Zhu (Soil Dynamics and Earthquake Engineering, 2026)

Synergistic modification of wheat bran by fungal-enzymes: From wheat bran composition and properties modulation, gluten protein structure evolution, to wheat dough and noodle quality improvement - Mengyuan Li; Yanhua Li; Li Li; Xueling Zheng; Binghua Sun; Sen Ma (Food Chemistry, 2026)

Spatiotemporal evolution and potential drivers of black soil development in Northeast China: A synthesis of multi-proxy geological records - Bing Liu; Xiao Zheng; Heqiang Du; Sen Li; Xiaolei Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Activated carbon-quartz sand dual-layer filter material accelerates the start-up of filter: Performance and mechanism - Sen Yang; Dong Li; Hongpeng Li; Jifang Zheng; Yanjun Zhu; Sibo Fu; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2026)

Characterizing brain structural and functional abnormalities in borderline personality disorder by seed-based d mapping approach - Wanru Qiu; Sen Li; Aoxue Zhang; Hao Yu; Jian Cui; Yinghong Xu; Liangliang Ping; Hao Zheng; Chunyu Dong; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2026)

Seepage response analysis method for levees considering soil parameter uncertainty and fluid‒solid coupling effects - Chenfei Shao; Sen Zheng; Kang Zhang; Yanxin Xu; Xing Li (Computers and Geotechnics, 2026)

Static and dynamic responses of a novel UEST column under axial compression and wave force - Yun-Long Chen; Jing-Zhong Tong; Li-Sen Zheng; Chao-Qun Yu (Ocean Engineering, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Does a positive culture correlate with the volume of synovial fluid inoculated into blood culture bottles for the diagnosis of periprosthetic joint infection? - Jia-Zheng Xu; Zhi-Sen Gao; Zhen Zhang; Ping Song; Wei Chai; Rui Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Influence of saturation on the dynamic response of shallow-buried tunnel in unsaturated porous media under SV wave incidence: Coupled effects of incident angle, porosity, and frequency - Zhe Yang; Weihua Li; Yexin Wan; Sen Zheng; Sainan Zhu (Tunnelling and Underground Space Technology, 2026)

Effect of saponin extracts of quinoa on postharvest preservation of asparagus and its mechanism - Jiehan Zhang; Sen Li; Qianqian Wang; Yao Lu; Wei Zheng; Yu Zhang; Xiao Guan (Journal of Stored Products Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Development of a prototype Compton camera consisting of high-resolution scintillator detectors - Sen Yang; Youchi Zhang; Yingdu Liu; Haonan Li; Pengshuo Gan; Samuel Mungai; Pengwei Shu; Zhonghua Kuang; Ning Ren; Yongfeng Yang; Zheng Liu (Physical and Engineering Sciences in Medicine, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Effects of groundwater level variation on the seismic response of sites with stratified saturated - unsaturated porous media overlying bedrock - Yexin Wan; Weihua Li; Zhe Yang; Sen Zheng; Sainan Zhu (Soil Dynamics and Earthquake Engineering, 2026)

Small-strain stiffness of in situ granite residual soil: Experimental comparison under biased and isotropic consolidation - Song Yin; Ya He; Sen Li; Siyue Zheng; Xianwei Zhang; Xinming Li (Soil Dynamics and Earthquake Engineering, 2026)

Seismic characterization of ancient lacustrine source-to-sink systems in a rift basin: The Bozhong Depression, Bohai Bay Basin, China - Xiaobo Zheng; Hongtao Zhu; Sen Li; Haifeng Yang; Zhiwei Zeng; Zhongheng Sun (Marine and Petroleum Geology, 2026)

Phytochemical analysis and cardiovascular protective effect of four herbal medicines with functional food properties ( Four Huaiqing Chinese Medicine ) - Yan Li; Xiaofei Xue; Meng Peng; Xiaolin Zheng; Sen Guo; Hailong Tao (Natural Product Research, 2025)

Climate-sensitive chemical weathering feedbacks in a Glacial River Basin, Northeast Qinghai-Tibet Plateau - Zheng Li; Jun Zhong; Shuai Chen; Xiang Qin; Sen Xu; Si-Liang Li (Global and Planetary Change, 2025)

Cellular indexing of transcriptomes and epitopes by sequencing unveils coordinated RNA and protein landscape in ovary at single-cell resolution - Yujuan Qi; Yuxuan Feng; Xiaoyan Liu; Jiaxin Li; Qiuru Huang; Zhenbei Li; Sen Zheng; Ning Chen; Jie Cheng; Xinhui Yang; Wei Tao; Xiangnan Cao; et al. (Chemical Engineering Journal, 2025)

Interpretation Analysis of Influential Variables Dominating Impulse Waves Generated by Landslides - Xiaohan Xu; Peng Qin; Zhenyu Li; Jiangfei Wang; Yuyue Zhou; Sen Zheng; Zhenzhu Meng (Journal of Marine Science and Engineering, 2025)
Landslide impacts into water generate impulse waves that, in confined basins and along steep coasts, escalate swiftly into hazardous near-shore surges. In this study, we present a scenario-aware workflow using gradient boosting and k-means clustering, and explain them using Shapley additive explanations (SHAPs). Two cases are addressed: forecasting at water entry (Scenario I) with predictors Froude number Fr, relative effective mass M, and relative thickness S; and pre-event assessment (Scenario II) with predictors Bingham number Bi, relative moving length L, and relative initial mass Mi. Using 270 controlled physical-model experiments, we benchmark six learning algorithms under 5-fold cross-validation. Gradient boosting delivers the best overall accuracy and cross-scenario robustness, with XGBoost close behind. Scenario I attains a coefficient of determination R2 of 0.941, while Scenario II achieves R2=0.865. Residual analyses indicate narrower spreads and lighter tails for the top models. SHAP reveals physics-consistent controls: M and Fr dominate Scenario I, whereas initial mass and the Bi dominate Scenario II; interactions Fr×S and Mi×Bi clarify non-linear amplification of wave amplitude and height. The cluster–predict–explain framework couples predictive skill with physical transparency and is directly applicable to coastal hazard screening and integration into shoreline early-warning workflows.

Wave scattering by a buried cavity in an unsaturated porous half-space - Zhe Yang; Weihua Li; Yexin Wan; Sen Zheng; Sainan Zhu (Soil Dynamics and Earthquake Engineering, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Synergistic dewatering of construction foundation sludge via tripartite strategy: High-efficiency flocculation and floc skeleton reinforcement mechanism - Shixin Zhang; Jiahui Zhang; Dilin He; Yixin Zhang; Shiyu Yuan; Xiaomin Tang; Huaili Zheng; Sen Li; Yuxin Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2025)

Genetic and histological characterization of a dwarf mutant in melon (Cucumis melo L.) reveals potential for breeding semi-dwarf cultivars - Zhuoxi Han; Wanning Zheng; Yang Li; Qingqing Ou; Haipeng Zhao; Han Zhao; Ju Xu; Sen Chai; Xueyong Yang; Zhonghua Zhang; Jinjing Sun (Theoretical and Applied Genetics, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Analytical analysis on the influence of groundwater level variation on seismic ground motion under plane wave incidence - Yexin Wan; Weihua Li; Sen Zheng; Zhe Yang; Sainan Zhu (Computers and Geotechnics, 2025)

Disruptions of white matter in adolescents with internet game disorder: evidence from seed-based d mapping - Hao Zheng; Chunyu Dong; Yu Wan; Hailong Shen; Sen Li; Shanling Ji; Jian Cui; Kun Li; Hao Yu; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

A novel flocculant based on "happy molecules" for the efficient removal of NSAIDs and NOM complexes: Role of parallel π-π stacking force - Shixin Zhang; Wenli Li; Yu Qin; Yao Chen; Zhen Liu; Sen Li; Longqing Tang; Huaili Zheng; Xiaomin Tang (Journal of Hazardous Materials, 2025)

Decoding the effect of antibiotics on biofilm formation in biofilters - Sen Yang; Dong Li; Sibo Fu; Jifang Zheng; Yanjun Zhu; Hongpeng Li; Huiping Zeng; Jie Zhang (Journal of Environmental Management, 2025)

Advancing autotrophic nitrogen removal in low C/N ratio wastewater: Innovative application of supercapacitor to enhance microbial electrolysis cells - Sen Fan; Yuhan Song; Decong Zheng; Xinyuan Peng; Sitao Li; Ping Gao; Daping Li (Journal of Environmental Sciences, 2025)

Study on multi-objective joint optimization of water and sediment operation considering multiple uncertainties: a case study in the lower yellow river - Fangzheng Zhao; Peng Yi; Ping-an Zhong; Xinyu Wan; Jieyu Li; Sen Wang; Weiyi Shi; Xinyu Wang; Ke Zheng (Stochastic Environmental Research and Risk Assessment, 2025)

Studies on the formation mechanism and multiscale structure of wheat bran dietary fiber-gluten protein complex - Mengyuan Li; Sen Ma; Xueling Zheng; Li Li (Food Bioscience, 2025)

Wave propagation in an ocean site considering fractional viscoelastic constitution of porous seabed - Sen Zheng; Weihua Li; Yexin Wan; Zhe Yang; Sainan Zhu (Computers and Geotechnics, 2025)

Effects of different dietary binders on growth, body composition, intestinal barrier and target of rapamycin pathway of juvenile largemouth bass (Micropterus salmoides) - Ye Gong; Zheng Chen; Runwei Miao; Shiwen Chen; Zhang Sen; Xuxiong Huang; Naisong Chen; Songlin Li (Animal Feed Science and Technology, 2025)

Microbial flocculants for removing multiple pollutants in wastewater: A review of recent trends and perspectives - Sen Li; Jiahui Zhang; Yan Liu; Nanchuan Song; Wenli Li; Longqing Tang; Huaili Zheng; Yixin Zhang; Yuxin Chen; Shixin Zhang (Journal of Water Process Engineering, 2025)

Constraints of upper crust magmatic processes on the formation of Saindak porphyry Cu deposit: Insights from mineral geochemistry - Lu Wang; Zi-xuan Wang; Yuan-chuan Zheng; Zeng-qian Hou; Zhu-sen Yang; Chang-da Wu; Xin Li (Lithos, 2024)

Adaptation mechanisms and efficiency of anammox bacterial aggregates in various reactor systems during the start-up period - Yanjun Zhu; Dong Li; Sibo Fu; Hongpeng Li; Sen Yang; Jifang Zheng; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2024)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Contribution assessment and accumulation prediction of heavy metals in wheat grain in a smelting-affected area using machine learning methods - Lingkun Meng; Anxu Sheng; Liu Cao; Mingyue Li; Gang Zheng; Sen Li; Jing Chen; Xiaohui Wu; Zhemin Shen; Linling Wang (Science of The Total Environment, 2024)

Transverse and longitudinal seismic responses of a subsea shield tunnel under obliquely incident seismic waves considering structure-water-poroelastic sediment-rock dynamic interactions - Weihua Li; Yexin Wan; Hang Mu; Sen Zheng (Ocean Engineering, 2024)

Selective benzene hydroalkylation: Ni/Ni PS/HY catalysts for enhanced cyclohexylbenzene formation - Wenhan Chen; Sen Zhao; Ley Boon Sim; Jianjun Li; Xianghua Liu; Jile Fu; Nuowei Zhang; Jinbao Zheng; Binghui Chen (Fuel, 2024)

Self-cleaning and multi-active sites amphoteric composite sponges: Efficient removal, selective adsorption and photocatalyst substrates of dyes - Qiang Yang; Jing Guo; Qiang Yao; Sen Zhang; Shi Feng; Fucheng Guan; Zheng Li; Xin Zhang; Yi Xu; Jiahao He (Chemical Engineering Journal, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Comparative proteomics reveal the humoral immune rejection of pearl oyster Pinctada fucata to xenograft from Pinctada maxima - Pei Wang; Ying Guo; Suping Li; Yusi Zheng; Tao Li; Sen Zhao; Dahui Yu; Lirong Bai (Aquaculture, 2024)

Predicting sulfide precipitation in magma oceans on Earth, Mars and the Moon using machine learning - J. ZhangZhou; Yuan Li; Proteek Chowdhury; Sayan Sen; Urmi Ghosh; Zheng Xu; Jingao Liu; Zaicong Wang; James M.D. Day (Geochimica et Cosmochimica Acta, 2024)

Effects of nitrogen supply on hydrogen-oxidizing bacterial enrichment to produce microbial protein: Comparing nitrogen fixation and ammonium assimilation - Haoran Wang; Lixia Zhang; Chang Tian; Sen Fan; Decong Zheng; Yuhan Song; Ping Gao; Daping Li (Bioresource Technology, 2024)

Effect of Fe(II) on manganese removal in biofilters: Microbial community, formation of manganese oxide and related mechanisms - Jifang Zheng; Dong Li; Huiping Zeng; Sen Yang; Zhaoxiang Zhang; Jie Zhang (Journal of Water Process Engineering, 2023)

Rapid start-up of the biofilter for simultaneous manganese and ammonia removal at low temperature: Effects of phosphate and copper - Jifang Zheng; Dong Li; Huiping Zeng; Sen Yang; Yanjun Zhu; Jie Zhang (Journal of Cleaner Production, 2023)

A state-of-the-art analysis of pharmacological delivery and artificial intelligence techniques for inner ear disease treatment - Wanqing Li; Nan Zheng; Qiang Zhou; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Huajun Zhao; Sen Lin (Environmental Research, 2023)

Thermal Contact Resistance of Granite Joints Under Normal Stress - Zheng-Wei Li; Meng-Cheng Long; Peng Xu; Chuan-Yuan Huang; Yun-Sen Wang (Rock Mechanics and Rock Engineering, 2023)

Influence of different loads on PCDD/F removal by SCR during municipal solid waste incineration - Jiayao Wu; Yuxuan Ying; Yunfeng Ma; Sen Zheng; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Chemosphere, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Preparation and numerical simulation of food gum electrospun nanofibers - Yihang Zhang; Jing Guo; Fucheng Guan; Jun Tian; Zheng Li; Sen Zhang; Miao Zhao (Journal of Food Engineering, 2023)

A highly selective SERS chip for rapid detection of copper ions in aquatic system - Qiangting Zheng; Qinyi Li; Sen Hu; Xiaoyu Guo; Haifeng Yang (Journal of Environmental Chemical Engineering, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Exact artificial boundary condition and 1D time-domain method for seismic response analysis of layered saturated poroelastic half-space - Weihua Li; Sen Zheng; Shaoxiong Mu; Hang Mu; Yexin Wan (Soil Dynamics and Earthquake Engineering, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Transcriptome analysis reveals the molecular mechanism of cinnamaldehyde against Bacillus cereus spores in ready-to-eat beef - Peng Guan; Yuting Chang; Sen Li; Xiaojie Wang; Zijie Dong; Weitao Zhou; Qi Zheng; Zhongmin Huang; Biao Suo (Food Research International, 2023)

Spying on the peroxynitrite fluctuation during hearing loss enabled by rationally designed fluorescent carbon dots - Haifang Liu; Jianbo Liu; Sen Zhang; Yun Chen; Juanli Zhang; Yuanqiang Sun; Zhenyu Zheng; Sang Hu; Zhaohui Li; Wenxue Tang (Chemical Engineering Journal, 2023)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Arsenopyrite oxidative dissolution in NaCl solution at high-temperature and high-pressure conditions: kinetics, pathways, dissolution mechanism and geological implications - Qingyou Liu; Kai Zheng; Shuai Wang; Luying Wang; Sen Lin; Heping Li (Contributions to Mineralogy and Petrology, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Indian Ocean tripole mode and its associated atmospheric and oceanic processes - Yazhou Zhang; Jianping Li; Sen Zhao; Fei Zheng; Juan Feng; Yang Li; Yidan Xu (Climate Dynamics, 2020)
Differing from the Indian Ocean dipole (IOD) that has sea surface temperature anomalies (SSTAs) of opposing signs over the tropical southeastern and western Indian Ocean, a tripole pattern, characterized by positive (negative) SSTAs over the tropical central (southeastern and western) Indian Ocean, is observed and named the Indian Ocean tripole (IOT). This study proposes the concept of the IOT and further investigates the associated atmospheric and oceanic processes. Using empirical orthogonal function (EOF) analysis, the IOT (IOD) is represented by the third (second) leading mode of the monthly SSTAs in the tropical Indian Ocean, explaining about 8.2% (10.3%) of the total variance. The IOT peaks in boreal summer, while the IOD has its mature phase in boreal fall. The spatio-temporal differences, together with the significant separation of these two EOF patterns, illustrate that the IOT is independent of the IOD. Heat budget diagnoses indicate that the anomalous temperature over the southeastern and western Indian Ocean is mainly generated by the net heat flux during April–May and by the total ocean advection in June–August. In contrast, the anomalous temperature is mainly driven by the advection of the mean temperature by the anomalous current in April and the residual term in May–June over the central Indian Ocean, which is replaced by advection of the anomalous temperature by the mean zonal current in July.

Advances in low-frequency ultrasound combined with microbubbles in targeted tumor therapy - Li-ying Wang; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2019)

Interhemispheric influence of Indo-Pacific convection oscillation on Southern Hemisphere rainfall through southward propagation of Rossby waves - Sen Zhao; Jianping Li; Yanjie Li; Fei-Fei Jin; Jiayu Zheng (Climate Dynamics, 2019)

Influence of the May Southern annular mode on the South China Sea summer monsoon - Ting Liu; Jianping Li; YanJie Li; Sen Zhao; Fei Zheng; Jiayu Zheng; Zhixiong Yao (Climate Dynamics, 2018)

Two leading modes of the interannual variability in South American surface air temperature during austral winter - Yanjie Li; Jianping Li; Fred Kucharski; Jin Feng; Sen Zhao; Jiayu Zheng (Climate Dynamics, 2018)

T follicular regulatory cells infiltrate the human airways during the onset of acute respiratory distress syndrome and regulate the development of B regulatory cells - Hongqiang Li; Runv Zhou; Chunmei Wang; Yusheng Li; Guizhen Zheng; Sen Jiang; Tiancao Dong; Jianwen Bai; Shumin Xu (Immunologic Research, 2018)

Advances in predicting the prognosis of hepatocellular carcinoma recipients after liver transplantation - Li-ying Wang; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2018)

A mutant in the CsDET2 gene leads to a systemic brassinosteriod deficiency and super compact phenotype in cucumber (Cucumis sativus L.) - Shanshan Hou; Huanhuan Niu; Qianyi Tao; Shenhao Wang; Zhenhui Gong; Sen Li; Yiqun Weng; Zheng Li (Theoretical and Applied Genetics, 2017)

Origin and classification of geothermal water from Guanzhong Basin, NW China: Geochemical and isotopic approach - Zhiyuan Ma; Xiucheng Li; Huiju Zheng; Jingbin Li; Bei Pei; Sen Guo; Xuelian Zhang (Journal of Earth Science, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Four genetic variants interact to confer susceptibility to atopic dermatitis in Chinese Han population - Changbing Shen; Longdan Liu; Zengqiong Jiang; Xiaodong Zheng; Li Meng; Xianyong Yin; Jing Gao; Yujun Sheng; Jingping Gao; Yang Li; Fusheng Zhou; Fengli Xiao; et al. (Molecular Genetics and Genomics, 2015)

Influence of dietary taurine and housing density on oviduct function in laying hens - Bin Dai; Yuan-shu Zhang; Zi-li Ma; Liu-hai Zheng; Shuang-jie Li; Xin-hong Dou; Jian-sen Gong; Jin-feng Miao (Journal of Zhejiang University-SCIENCE B, 2015)

Anti-inflammatory Effects of Propofol on Lipopolysaccharides-Treated Rat Hepatic Kupffer Cells - Sen Li; Chun-xia Wang; Nai-zheng Liu; Ping Liu (Cell Biochemistry and Biophysics, 2015)

Lead accumulation and tolerance of Moso bamboo (Phyllostachys pubescens) seedlings: applications of phytoremediation - Dan Liu; Song Li; Ejazul Islam; Jun-ren Chen; Jia-sen Wu; Zheng-qian Ye; Dan-li Peng; Wen-bo Yan; Kou-ping Lu (Journal of Zhejiang University-SCIENCE B, 2015)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Grain-size characteristics of sediments formed since 8600 yr B.P. in middle reaches of Yarlung Zangbo River in Tibet and their paleoenvironmental significance - Yinghua Zheng; Yongqiu Wu; Sen Li; Lihua Tan; Shiwei Gou; Hongyan Zhang (Chinese Geographical Science, 2009)

A wind tunnel simulation of the dynamic processes involved in sand dune formation on the western coast of Hainan Island - Sen Li; Xianwan Liu; Huichuan Li; Yinghua Zheng; Xinghu Wei (Journal of Geographical Sciences, 2007)

A novel bieremophilanolide from Ligularia lapathifolia - Yun-Sen Li; Shao-Shun Li; Zheng-Tao Wang; Shi-De Luo; Da-Yuan Zhu (Natural Product Research, 2006)

Deposition of sandstorms in a vegetation-covered sand dune in Ejin Oasis and its characteristics - Xiaohao Wen; Baosheng Li; Wei Wang; Sen Li; Xianjiao Ou; Yanming Zheng (Journal of Geographical Sciences, 2006)

Sensitized photooxidation of furanoeremophilane with singlet oxygen and their biogenetic relationship - Yun-Sen Li; Zheng-Tao Wang; Shi-De Luo; Shao-Shun Li; Da-Yuan Zhu (Natural Product Research, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)